2022
DOI: 10.1111/and.14408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atorvastatin on erectile dysfunction: A meta‐analysis and systematic review

Abstract: Atorvastatin may be an effective treatment for erectile dysfunction (ED). The purpose of this meta‐analysis was to determine whether atorvastatin therapy is effective in the treatment of ED. All published research on atorvastatin in the treatment of ED patients in EMBASE, PubMed, Web of Science and Cochrane were investigated till 30 October 2021. A meta‐analysis of randomized controlled trials (RCTs) was done to investigate the efficacy of atorvastatin and placebo in the treatment of ED. Moreover, we also perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In patients with severe ED conditions, especially those with a rapid decline in sexual function in the short term, which suggests that lipid parameters are in a state of rapid change, endothelial dysfunction to atherosclerosis occurs rapidly, the trend is more acute, and the likelihood of CAD in a short period of time is also greater. Currently, it is recommended that patients undergo early CVD-related examinations; the use of statin interventions can effectively reduce the risk of CVD, and at the same time, ED and have a therapeutic effect on ED at the same time ( 42 ). Guidelines recommend that exercise stress testing (EST), carotid intima-media thickness (CIMT), and noninvasive assessment of endothelial function are effective methods for assessing individual cardiovascular risk after ED ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with severe ED conditions, especially those with a rapid decline in sexual function in the short term, which suggests that lipid parameters are in a state of rapid change, endothelial dysfunction to atherosclerosis occurs rapidly, the trend is more acute, and the likelihood of CAD in a short period of time is also greater. Currently, it is recommended that patients undergo early CVD-related examinations; the use of statin interventions can effectively reduce the risk of CVD, and at the same time, ED and have a therapeutic effect on ED at the same time ( 42 ). Guidelines recommend that exercise stress testing (EST), carotid intima-media thickness (CIMT), and noninvasive assessment of endothelial function are effective methods for assessing individual cardiovascular risk after ED ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment with these drugs could also be effective in the treatment of patients with ED non-responders to phosphodiesterase type 5 inhibitor administration [ 116 ]. A recent meta-analysis seems to confirm these aspects, showing that atorvastatin is able to improve erectile function in patients both alone or in combination with other treatments for ED [ 117 ].…”
Section: Vitamin D and Erectile Dysfunction: Relationship With Hyperc...mentioning
confidence: 97%
“…However, some observational studies have yielded contrary results. Hao Su et al conducted a meta-analysis of randomized controlled trials (RCTs) and single-arm trials (SATs), nding that the International Index of Erectile Function-5 scores were higher in the atorvastatin treatment group compared to the control group, suggesting atorvastatin is an effective treatment for ED patients (11) . A cohort study of Taiwanese males aged 40-79 using statin drugs found that atorvastatin intake could reduce the risk of new-onset ED, and this effect was dose-and durationdependent (12) .…”
Section: Introductionmentioning
confidence: 99%